2015
DOI: 10.1021/acs.orglett.5b01096
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Promoted and One-Pot Synthesis of Phenanthridines and Quinolines from Aldehydes and O-Acyl Hydroxylamine

Abstract: A one-pot synthesis of phenanthridines and quinolines from commercially available or easily prepared aldehydes has been reported. O-(4-Cyanobenzoyl)hydroxylamine was utilized as the nitrogen source to generate O-acyl oximes in situ with aldehydes catalyzed by Brønsted acid. O-Acyl oximes were then subjected to visible light photoredox catalyzed cyclization via iminyl radicals to furnish aza-arenes. A variety of phenanthridines and quinolines have been prepared assisted by Brønsted acid and photocatalyst under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(40 citation statements)
references
References 72 publications
0
39
0
Order By: Relevance
“…193 Yu employed a catalytic amount of p -chlorobenzenesulfonic acid in the photocatalytic synthesis of azaarenes, presumably to facilitate formation of an acyl oxime precursor rather than to influence PET. 194 Qi and Zhang found that catalytic TsOH improved their synthesis of α-alkoxybenzamides. 195 König observed improved performance of photocatalytic amine deprotection at low pH, though the mechanistic basis of this effect was not determined.…”
Section: Photoinduced Electron Transfermentioning
confidence: 99%
“…193 Yu employed a catalytic amount of p -chlorobenzenesulfonic acid in the photocatalytic synthesis of azaarenes, presumably to facilitate formation of an acyl oxime precursor rather than to influence PET. 194 Qi and Zhang found that catalytic TsOH improved their synthesis of α-alkoxybenzamides. 195 König observed improved performance of photocatalytic amine deprotection at low pH, though the mechanistic basis of this effect was not determined.…”
Section: Photoinduced Electron Transfermentioning
confidence: 99%
“…3‐(Trifluoromethyl)phenanthridine (3v): 23 Compound 3v was prepared according to the general experimental procedure as above, yield 0.210 g (85 %); white solid. 1 H NMR (500 MHz, CDCl 3 ): δ = 9.29 (d, J = 7.6 Hz, 1 H), 8.42–8.65 (m, 2 H), 7.96–8.14 (m, 2 H), 7.80–7.96 (m, 1 H), 7.65–7.80 (m, 1 H), 7.50 (s, 1 H) ppm.…”
Section: Methodsmentioning
confidence: 99%
“…Yu and An have developed an intermolecular one-pot C-N coupling of aldehydes and O-acyl hydroxylamines to give phenanthridines and quinolines (Scheme 61). 64 The in situ reaction between aldehydes and O-acyl hydroxylamines would give O-acyl oximes for the generation of iminyl radicals. Further cyclization would then take place and furnish the desired aza-arenes.…”
Section: Intermolecular Cyclizationmentioning
confidence: 99%